2019
DOI: 10.37358/rc.19.6.7315
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Intensive Educational Program Regarding Preeclampsia on Health Professional Knowledge

Abstract: Preeclampsia is a multi-system disorder unique to human pregnancy with multi-system involvement. Worldwide, it causes ]500,000 fetal and neonatal deaths and ]70,000 maternal deaths every year. Limited knowledge of health professionals in direct connection with complications of pregnancy, and inability to keep up with medical knowledge, has potentially severe effects on the quality of care and increases maternal and perinatal mortality. The aim has been to identify the impact of an intensive educational program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…However, the primary health nurses got the lowest average mean of 2.70 to the maternal effects of pre-eclampsia. Similarly, research has found that health professionals have limited knowledge about pre-eclampsia and eclampsia among midwives and doctors caring for pregnant women with pregnancy induced hypertension [10].…”
Section: Knowledgeablementioning
confidence: 99%
See 1 more Smart Citation
“…However, the primary health nurses got the lowest average mean of 2.70 to the maternal effects of pre-eclampsia. Similarly, research has found that health professionals have limited knowledge about pre-eclampsia and eclampsia among midwives and doctors caring for pregnant women with pregnancy induced hypertension [10].…”
Section: Knowledgeablementioning
confidence: 99%
“…Although it range under knowledgeable, this suggest that educational program to increase their level of knowledge. The development and implementation of educational training program can increase the level of knowledge of healthcare professionals [10].…”
Section: Average Mean 286 Knowledgeablementioning
confidence: 99%